Rapid detection of Hemophilus influenzae and Streptococcus pneumoniae simultaneously using a duplex recombinase-aided amplification assay directly from invasive clinical samples - Zhou, Lin; Xia, Yuyan; Feng, Yanling; Du, Bing; Huang, Xianyi; Xu, Wenjian; Li, Jing; Fang, Fang; Meng, Chun; Yu, Li; Ma, Lijuan; Xue, Guanhua; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCommunity-acquired pneumonia (CAP) remains a leading cause of mortality in children under five years of age worldwide. Streptococcus pneumoniae and Haemophilus influenzae are the most common bacterial pathogens causing CAP that requires hospitalization, highlighting the critical need for a simple, low-cost, and highly sensitive method for rapid diagnosis.MethodsWe developed a duplex recombinase-aided amplification (RAA) assay for the simultaneous detection of S. pneumoniae and H. influenzae. Following comparative genomic analysis, the conserved lytA gene and omp6 gene were selected as the specific targets for S. pneumoniae and H. influenzae, respectively. The reaction conditions, including temperature and probe concentration, were optimized.ResultsThe established duplex RAA assay can be completed within 10 minutes at a constant temperature of 39°C, with an optimal probe concentration combination of 0.6 μM for S. pneumoniae and 0.8 μM for H. influenzae. The assay demonstrated high sensitivity, with a limit of detection of 72 copies per reaction for S. pneumoniae and 35 copies per reaction for H. influenzae.DiscussionThis study presents a rapid and accurate nucleic acid amplification assay for the concurrent detection of two major bacterial pathogens in childhood CAP. The speed, simplicity, and sensitivity of the duplex RAA assay make it a promising tool for early and rapid etiological diagnosis in clinical settings.